Estructura y transferencia de la propiedad comunal de Colalao y Tolombón (provincia de Tucumán) en la segunda mitad del siglo XIX - Fandos, Cecilia (Centro de Historia Argentina y Americana, 2007)
In this work is studied the division process of communal property of Colalao y Tolombón natives in the province of Tucumán between 1870 y 1890 in the context of the sugar advancement, with the correspondent development of the capitalist structures. It was reconstructed the evolution of the agrarian structure, it was inquired about the ways of distribution of the communal territories, it was determined the number and surnames of the original owner families before and after the division of land and, at least, it was sounded the different characteristics of buyers and sellers of the communal land.